Abrasive wear in hard thin films coated dies in hot extrusion aluminum - Herrera, J.; Martínez, D.; González, R.; Rodríguez, J. (Universidad Autónoma de Nuevo León, 2012)
Abrasive wear resistance of hot extrusion AISI H13 coated dies used to produce extruded aluminum micro multivoid tubes was studied. In this process, aluminum and dies are constantly under high friction conditions producing premature die wear; aluminum or lubricant adherence on die surface layer, is caused by this phenomenon with product rejection as a consequence. The hot extrusion dies most important properties are hot hardness, wear resistance and suface finishing. Extrusion dies coated with hard thin films coatings by physical vapor deposition, PVD and chemical vapor deposition , CVD, were utilized and thermal diffusion treatment as an altrnative. The thin film coatings mechanical properties, nano indentation, and SEM surface analysis were performed to characterize coatings and dies. The wear mechanism was determined and it is affected by the die contact suface layer finished by electropolishing and the dies coated with thermal diffusion treatment was the most resistance condition to the wear process due to the presence of V and Nb carbonitrures.